Magnetic field-induced vertigo in the MRI environment - Glover, Paul (Springer, 2015)
This review discusses the theory behind, and the experimental evidence for, the perception of vertigo in a high magnetic field found in a magnetic resonance imaging (MRI) environment. Recent experiments have shown that there is an eye nystagmus response that is proportional to magnetic field exposure and not purely one of rate of change of magnetic field. The mechanism of transduction can be attributed to the Lorentz forces on the endolymph in the ear canals, producing a static pressure due to the vector product of the magnetic field and current density. The adaption and response of the measurable effect reveals time constants which support such a mechanism and explain why the balance system responds in the way we observe and feel. The position and movement of the head relative to the direction of field is of fundamental importance to the sensation of vertigo, as are ambient conditions such as lighting levels. Recent surveys of subjects undergoing seven tesla or higher MRI scans report that although there is a high perception of vertigo-like effects, these are not intolerable and are not generally the cause of subject withdrawal. This review argues that the International Commission on Non-Ionizing Radiation guidelines on low-frequency fields still need to acknowledge the role of a high magnetic field in producing vertigo sensations rather than rate of change of field alone.